2015
DOI: 10.1121/1.4922328
|View full text |Cite
|
Sign up to set email alerts
|

Auditory attention strategy depends on target linguistic properties and spatial configuration

Abstract: Whether crossing a busy intersection or attending a large dinner party, listeners sometimes need to attend to multiple spatially distributed sound sources or streams concurrently. How they achieve this is not clear-some studies suggest that listeners cannot truly simultaneously attend to separate streams, but instead combine attention switching with short-term memory to achieve something resembling divided attention. This paper presents two oddball detection experiments designed to investigate whether directin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 38 publications
2
11
0
Order By: Relevance
“…Unlike the dual-task conditions, there was little congruency effect for the single-task conditions. A similar difference has been reported for an auditory detection task (McCloy & Lee, 2015). This divergence has been studied in the more cognitive speeded dual-task literature (e.g.…”
Section: Relation To the Prior Literaturesupporting
confidence: 80%
See 3 more Smart Citations
“…Unlike the dual-task conditions, there was little congruency effect for the single-task conditions. A similar difference has been reported for an auditory detection task (McCloy & Lee, 2015). This divergence has been studied in the more cognitive speeded dual-task literature (e.g.…”
Section: Relation To the Prior Literaturesupporting
confidence: 80%
“…This is for both single-task conditions and dual-task conditions, and is in contrast with Gabor detection where there were larger congruency effects for the dual-task conditions. To our knowledge, the most similar result are the reduced congruency effects found in audition by McCloy and Lee (2015) for semantic versus phonetic tasks.…”
Section: Relation To the Prior Literaturesupporting
confidence: 59%
See 2 more Smart Citations
“…For example, when more detailed spatial information can be provided regarding the location of each speaker, as in the case of audio-visual speech (Blackburn et al, 2019) or spatial cueing, spatial attention might be engaged. Indeed, (Kopco et al, 2010) demonstrated that giving participants information regarding the location of potential maskers assisted selective-attention performance, although the benefit depended on the specific spatial configuration (see also Jones and Litovsky 2008; McCloy and Lee 2015). Similarly, (Ihlefeld and Shinn-Cunningham, 2008a) report an advantage of spatial separation on selective attention performance, but only when participants were explicitly told to attend to a particular location, whereas when attention was directed towards an acoustic feature, no advantage was observed for spatial separation.…”
Section: Discussionmentioning
confidence: 99%